10 W low-noise green laser generation by the single-pass frequency doubling of a single-frequency fiber amplifier. (19th June 2020) - Zeng, Xin; Cui, Shuzhen; Qian, Jiaping; Cheng, Xin; Dong, Jinyan; Zhou, Jiaqi; Xu, Zhen; Feng, Yan
Abstract: A high-power low-noise continuous-wave green laser at 532 nm is developed by the single-pass frequency doubling of a single-frequency 1064 nm Yb-doped fiber amplifier in a MgO-doped periodically-poled stoichiometric lithium tantalate crystal. More than 10 W is obtained with a conversion efficiency of 38.3%. The linewidth of the green laser is estimated at about 3.4 kHz according to the linewidth of 1.7 kHz of the fundamental laser. The relative intensity noise integrated from 100 Hz to 10 MHz is less than 0.03%. The laser is a promising candidate for applications in quantum simulation with ultracold atoms and the pumping of Ti:sapphire lasers etc.